Moluscos del Perú - Ramírez, Rina (2003)
Peru is an ecologically diverse country, with 84 life zones in the Holdridge system and 18 ecological regions (including two marine). 1910 molluscan species have been recorded. The highest number corresponds to the sea: 570 gastropods, 370 bivalves, 36 cephalopods, 34 polyplacoforans, 3 monoplacophorans, 3 scaphopods and 2 aplacophorans (total 1018 species). The most diverse families are Veneridae (57spp.), Muricidae (47spp.), Collumbellidae (40 spp.) and Tellinidae (37 spp.). Biogeographically, 56 % of marine species are Panamic, 11 % Peruvian and the rest occurs in both provinces; 73 marine species are endemic to Peru. Land molluscs include 763 species, 2.54 % of the global estimate and 38 % of the South American estimate. The most biodiverse families are Bulimulidae with 424 spp., Clausiliidae with 75 spp. and Systrophiidae with 55 spp. In contrast, only 129 freshwater species have been reported, 35 endemics (mainly hydrobiids with 14 spp. The paper includes an overview of biogeography, ecology, use, history of research efforts and conservation; as well as indication of areas and species that are in greater need of study.